2017
DOI: 10.1093/jjco/hyx022
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort during bronchoscopy performed after endobronchial intubation with fentanyl and midazolam: a prospective study

Abstract: Objective: Although endobronchial intubation during a bronchoscopic examination is useful for invasive procedures, it is not routine practice in Japan. The present study evaluated discomfort due to endobronchial intubation using fentanyl and midazolam sedation during bronchoscopy. Methods: Thirty-nine patients were enrolled prospectively from November 2014 to September 2015 at Okayama University Hospital. Fentanyl (20 µg) was administered to the patients just before endobronchial intubation, and fentanyl (10 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The JSRE Safety Measures Committee 2020 recommended the omission of throat spray anesthesia before bronchoscopic examination during the coronavirus disease 2019 pandemic, suggesting that sedation using the combination of an opioid and midazolam should be used to prevent aerosol generation. In fact, our previous study showed that throat anesthesia using Jackson's spray may lead to patient distress 6,7) . The omission of throat spray anesthesia may prevent aerosol generation and reduce patient distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JSRE Safety Measures Committee 2020 recommended the omission of throat spray anesthesia before bronchoscopic examination during the coronavirus disease 2019 pandemic, suggesting that sedation using the combination of an opioid and midazolam should be used to prevent aerosol generation. In fact, our previous study showed that throat anesthesia using Jackson's spray may lead to patient distress 6,7) . The omission of throat spray anesthesia may prevent aerosol generation and reduce patient distress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pethidine chloride, fentanyl, and propofol were used in 10.9%, 4.4%, and 4.2% of facilities 2) . The combination of an opioid (fentanyl or pethidine) and midazolam allowed the performance of safe bronchoscopy in a timely manner for Japanese patients [3][4][5][6][7][8] . The spray was administered directly into the oropharynx before the procedure and was an important prerequisite for the successful performance of brochoscopy 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Inadvertent oversedation sometimes causes respiratory depression and oxygen desaturation (17), although sedation is necessary and recommended for bronchoscopic procedures (11)(12)(13). It has been published that the nadir on SpO 2 decline could be delayed by 45-60 seconds after an apnea episode (18).…”
Section: Discussionmentioning
confidence: 99%
“…When fentanyl is administered with other sedatives, an initial dose of 25-50 μg is recommended with additional doses of 25 μg, as required, until the desired effect is achieved. The recommended dose of midazolam is 0.01-0.1 mg/kg (12,13). As Japanese are, on average, physically smaller than Westerners, we selected a lower dose of fentanyl.…”
Section: Bronchoscopy Proceduresmentioning
confidence: 99%
See 1 more Smart Citation